A randomized study of raisins versus alternative snacks on glycemic control and other cardiovascular risk factors in patients with type 2 diabetes mellitus. Issue 1 (April 2014) - Bays, Harold; Weiter, Kathy; Anderson, James
Abstract: Just as the type and duration of physical activity can have variable effects on the glucose levels and other cardiometabolic parameters among patients with type 2 diabetes mellitus (T2DM), so can the types of foods have variable effects as well. This 12-week randomized study of 51 study participants evaluated the impact of routine consumption of dark raisins versus alternative processed snacks on glucose levels and other cardiovascular risk factors among patients with type T2DM. In this study, compared to alternative processed snacks, those who consumed raisins had a significant 23% reduction in postprandial glucose levels ( P = 0.024). Also compared to snacks, those who consumed raisins had a 19% reduction in fasting glucose and 0.12% reduction in hemoglobin A1c, although these latter findings did not achieve statistical significance. Regarding blood pressure, compared to alternative processed snacks, those who consumed raisins had a significant 8.7 mmHg reduction in systolic blood pressure ( P = 0.035) (7.5% [ P = 0.031]) but did not experience a significant reduction in diastolic blood pressure. Compared to alternative processed snacks, those who consumed raisins did not have a significant improvement in body weight, body mass index, waist circumference, fasting insulin, homeostatic model assessment of insulin resistance, total cholesterol, low-density lipoprotein cholesterol, high-density lipoprotein cholesterol (HDL), triglyceride, or non-HDL cholesterol levels. Overall, these data support raisins as a healthy alternative compare to processed snacks in patients with T2DM.